THU0150 High Acute Phase Reactants Predict Cardiovascular Events and Rapid Radiological Progression in Inflammatory Arthritis. (23rd January 2014) - Balogh, E.; Ng, C. T.; Saber, T.; Dias, J. M.; Mullan, R.; Fearon, U.; Veale, D. J.
Abstract : Background: Inflammatory arthritis (IA) is associated with an increased risk of cardiovascular events 1, 2, similarly known that high baseline serum amyloid A (SAA) levels and erosive disease are predictors of aggressive arthritis 3 . Objectives: To assess the influence of markers of early disease activity on long term cardiovascular outcome and radiological progression in IA. Methods: Patients were recruited and prospectively followed for 4 years after commencing biological therapy (n=62). Radiological progression was estimated using Modified Sharp score (mSS) method at baseline, 3 months and 4 years posttherapy on hands and feet radiographs. Radiological progression was defined as ΔmSS>1.5 with a cutoff of rapid radiological progression at ΔmSS>30. Cardiovascular (CV) disease was defined as any new CV event during follow up. Markers of disease activity were collected at each timepoint including erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), tender joint count out of 28 joints (TJC28), swollen joint count out of 28 joints (SJC28) and patient global health assessment (PGH). Disease activity score 28 (DAS28) remission was defined by DAS28<2.6. Results: Median (range) patient age was 50, 5 (18-77) yrs with disease duration of 9.75 (0.3-48) yrs. Eight patients (13%) sustained CV events and they were older, had higher baseline CRP and SAA levels compared to those who did not (p=0.029, p=0.0001). Baseline CRP and SAA levels showed significant correlation with each other (all p<0.0001). Radiological progressor status deteriorated from 66.7 % (1st year) to 77% after 4 yrs. Patients with rapid radiological progression (RRP) at 4 yrs sustained more CV events (p=0.003), moreover they had higher baseline SAA (p=0.004) and CRP levels (NS) compared to nonprogressors. In addition, patients suffering CV events or RRP had higher 3 months DAS28 scores than non-progressors (p=0.013, p=0.001), probably due to higher ESR (p=0.005, p<0.0001) and SJC28 (p=0.009, p=0.012) at 3 months. RA patients in DAS28 remission at 3 months had no evidence of CV events or RRP in long term. Conclusions: In this extended inflammatory arthritis cohort, CV events and RRP appear to be predicted by high baseline SAA and CRP, suggesting a direct link to the initial level of inflammation. RA remission is not associated with CV events or RRP. References: Inflammatory arthritis as a novel risk factor for cardiovascular disease. John H, Kitas G. Eur J Intern Med. 2012 Oct;23(7):575-9. Traditional cardiovascular risk factors, inflammation and cardiovascular risk in rheumatoid arthritis. Liao KP, Solomon DH. Rheumatology (Oxford).2013 Jan;52(1):45-52. Serum amyloid A in the assessment of early inflammatory arthritis. Cunnane G, Grehan S, Geoghegan S, McCormack C, Shields D, Whitehead AS, Bresnihan B, Fitzgerald O. J Rheumatol. 2000 Jan;27(1):58-63. Acknowledgements: Translational Research Group, DAMC, SVUH Disclosure of Interest: E. Balogh Grant/research support from: MSD, C. Ng: None Declared, T. Saber: None Declared, J. Dias: None Declared, R. Mullan: None Declared, U. Fearon: None Declared, D. Veale Grant/research support from: Abbott, Opsona, Pfizer, Roche, Consultant for: MSD, Pfizer, Roche, Speakers bureau: Janssen, MSD, Pfizer, UCB